What matters for the decision to study abroad? A lab-in-the-field experiment in Cape Verde - Catia Batista; David M Costa; Pedro Freitas; Gonçalo Lima; Ana Balç\~ao Reis (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Study abroad migration is the fastest growing international migration flow. However, the college completion rates of students from low-income countries are often modest in OECD countries, raising the hypothesis that these migrants are poorly informed about the costs and benefits of their decision. Our work tests this hypothesis by running a lab-in-the-field experiment where graduating high school students in Cape Verde are faced with incentivized decisions to apply for college studies abroad. Our results show that potential migrants react strongly to information about the availability of financial support and about college completion rates. Since subjects' prior beliefs on availability of financial support are overestimated, it is likely that study migrants need to shift their time from study to work after uninformed migration, which likely harms their scholar performance. Policies that inform potential migrants of actual study funding possibilities should decrease study migration flows but are likely to improve successful graduation.
Keywords: O15; F22; J61; C91; 330; international study migration; lab-in-the-field experiment; education; information; uncertainty